Systemy informatyczne klasy workflow a orientacja procesowa przedsiębiorstwa - Adamczyk, Marek; Trzcieliński, Stefan (Workflow Computing System and Business Process Orientation, 2005)
The paper presents essence of the Business Process Orientation as a concept orientated on improvement of the business effectivenes. The boundaries for implementing the Business Process Orientation supported by Workflow computing system in company management caused by improper organizational structure are presented. Then, structure features which are conductive to BPO are indicated and analysed.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1081, s. 334-339